Transcriptomic and Metabolomic Data Reveal the Key Metabolic Pathways Affecting Streltzoviella insularis (Staudinger) (Lepidoptera: Cossidae) Larvae During Overwintering - Pei, Jiahe; Xu, Yabei; Zong, Shixiang; Ren, Lili (Frontiers in Physiology, 2021)
Streltzoviella insularis (Staudinger) (Lepidoptera: Cossidae) is a woodboring insect feeding on Fraxinus pennsylvanica, Sophora japonica, and Ginkgo biloba, as well as many other species used for urban greening and plain afforestation in northern China, including the temperate north. There is also a risk that S. insularis could spread through the transportation of seedlings, thereby increasing urban greening costs. However, how S. insularis increases the cold tolerance then reduces it to survive winter temperature below 0°C remains unclear. In the transcriptomic of S. insularis, we identified three profiles (profile 25, 27 and 13) whose trends related to the cold tolerance. We detected 1783 differentially expressed genes (in profile 25) with similar changes in the cold tolerance during the whole overwintering period, as well as six continuously up-regulated differentially expressed genes; we identified 522 genes from the above two enriched in the AMPK signaling pathway. The metabolome analysis identified 122 differential metabolites. Combining the transcriptome SI_1~12 KEGG enrichment analysis and metabolome SI_1~12 MetPA analysis, we identified four co-pathways, among which ‘Glycerophospholipid metabolism’ was the pathway most enriched in differentially expressed genes and differential metabolites. The AMPK signaling and glycerophospholipid metabolism pathways play key roles in the natural overwintering physiological process of S. insularis larvae.